Emerging role of exosomes in cancer therapy: progress and challenges - Jiale Li; Jiachong Wang; Zigui Chen (Molecular Cancer)
Abstract This review highlights recent progress in exosome-based drug delivery for cancer therapy, covering exosome biogenesis, cargo selection mechanisms, and their application across multiple cancer types. As small extracellular vesicles, exosomes exhibit high biocompatibility and low immunogenicity, making them ideal drug delivery vehicles capable of efficiently targeting cancer cells, minimizing off-target damage and side effects. This review aims to explore the potential of exosomes in cancer therapy, with a focus on applications in chemotherapy, gene therapy, and immunomodulation. Additionally, challenges related to exosome production and standardization are analyzed, highlighting the importance of addressing these issues for their clinical application. In conclusion, exosome-based drug delivery systems offer promising potential for future cancer therapies. Further research should aim to enhance production efficiency and facilitate clinical translation, paving the way for innovative cancer treatment strategies.